Propriedades vibracionais da L-Asparagina monohidratada sob pressões de até 30GPA - Silva, José de Arimatéa Freitas e (2012)
Crystalline materials where hydrogen bonds play fundamental roles have received great attention in the last years. Among these systems there are amino acids, which are molecules of great importance to the life. In this Thesis the vibrational properties of L-asparagine monohydrated (LAM) submitted to high pressure conditions through Raman spectroscopy between 30 and 3600 cm-1 are studied. The maximum pressure was 30 GPa, in fact, the highest pressure a cystalline amino acid was studied up to now. This points to a new paradigm because when many materials are submetted to pressure values of such a magnitude, they undergo an amorphization process, i.e., they lost long-order symmetry (as occurs, for example, with L-alanine that suffers amorphization at 15 GPa). Surprisely, LAM remain with a well defined crystal structure up to 30 GPa, although it presents na extraordinary sequence of phase transitions. A previous study showed the occurrence of three phase transitions for LAM between 0 e 2 GPa. In this work, when crystal was investigated in the range between 2 and 30 GPa, it was possible to infer that LAM undergoes five additional phase transitions in the following ranges: (i) 2,1 – 3,1 GPa; (ii) 4,7 – 6,6 GPa; (iii) 9,3 – 9,9 GPa; (iv) 15,0 – 17,0 GPa; (v) 22,4 – 25,1 GPa. The phase transitions in such a kind of system can be understood as molecular conformation in the unit cell; changes of the intermolecular hydrogen bonds; or structural changes with modification of the space group. From a careful analysis of the modifications of both external and internal modes of the crystal, it was possible to give a picture of the five different phase transitions undergone by LAM. One of these transitions, between 9,3 and 9,9 GPa, involving changes in all spectral range, clearly is related to a solid-solid phase transition with modification of the crystal space group. All phase transitions are reversible, because the original Raman spectrum is recovered when pressure is released from 30 GPa to atmospheric pressure. Analysis of the frequency of the mode associated to NH3 + as a function of pressure and the connection with dimensions of hydrogen bonds is furnished, as well as it is given a comparison of the present study with others already published in the literature. Finally, data related to experimental fittings d/dP of the frequency of all vibrational modes in the complete range of pressure is also furnished.